2020
DOI: 10.47381/aijre.v30i1.239
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Nursing and Allied Health Students Undertaking a Rural Placement: Barriers and Enablers to Satisfaction and Wellbeing

Abstract: Australia's rural health services commonly face serious and protracted workforce shortages. To help address such shortages in rural and remote areas, a range of programs exist to support university students to undertake placements in a rural setting. In particular, University Departments of Rural Health (UDRHs) are funded to support nursing and allied health students to undertake a rural placement. As UDRHs encourage students to 'go rural' and as they coordinate and facilitate placements in rural settings, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This finding is similar to Mak et al 11 who found that virtual placement experiences allow students to achieve clinical learning outcomes, but were not as effective in facilitating their affective and physical learning about the rural location. This reinforces that the physical and relational experiences on rural and remote placements are valued by students and important for their learning and enjoyment of their rural or remote placement 29 . Planning student connection with other students and the rural and remote community throughout placements is therefore important.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This finding is similar to Mak et al 11 who found that virtual placement experiences allow students to achieve clinical learning outcomes, but were not as effective in facilitating their affective and physical learning about the rural location. This reinforces that the physical and relational experiences on rural and remote placements are valued by students and important for their learning and enjoyment of their rural or remote placement 29 . Planning student connection with other students and the rural and remote community throughout placements is therefore important.…”
Section: Discussionmentioning
confidence: 57%
“…This reinforces that the physical and relational experiences on rural and remote placements are valued by students and important for their learning and enjoyment of their rural or remote placement. 29 Planning student connection with other students and the rural and remote community throughout placements is therefore important. This could be achieved through peer placements and embedding social and interprofessional learning activities into placement planning.…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the early COVID‐19 public health response included restrictions to reduce social interactions to limit the spread; these public health orders prevented students on rural placements from moving around the local area, restricted duties and social activities during the placement, and meant students were often alone in student accommodation 6 . Even in nonpandemic times, many health students on rural placements are removed from their social supports and likely experience feelings of isolation and loneliness due to this, ensuring students are able engage with the rural community and placement could mitigate some of these concerns 6,13 . However, COVID‐19 likely added multiple barriers to achieving such connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…Placement demands have been cited as an additional stressor that impacts well‐being, 12 with high levels of anxiety and stress reported by health care students around placements 12 . Rural placements have the potential to further impact mental health by increasing financial stress and isolating students from their social support structures 8,13 . These issues likely intensified during the emergence of the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation